Treatment of breast cancer patients from a public healthcare system in a private center: costs of care for a pilot public-private partnership in oncology - Kaliks, Rafael Aliosha (Einstein (Sao Paulo), 2013)
OBJECTIVE: To describe the flow and costs associated with the diagnosis and treatment of patients with breast cancer who come from the public healthcare system and were treated at Hospital Israelita Albert Einstein. METHODS: Between August 2009, and December 2011, 51 patients referred by the Unified Public Healthcare System (SUS) had access to Hospital Israelita Albert Einstein for diagnostic radiology, medical oncology, radiotherapy, and oncologic/ breast reconstruction surgery. The data were collected retrospectively from the hospital records, patient charts, pharmacy records, and from the hospital billing system. RESULTS: The total sum spent for diagnosis and treatment of these 51 patients was US$ 1,457,500.00. This value encompassed expenses with a total of 85 hospitalizations, 2,875 outpatient visits, 16 emergency room visits, and all expenses associated with these stays at the hospital. The expenditure for treatment of each patient submitted to biopsy, breast conserving surgery, adjuvant chemotherapy without trastuzumab (a regime with taxane followed by anthracycline), radiotherapy, and 5 years of tamoxifen was approximately US$ 25,500.00. CONCLUSION: Strategies for cost-reduction of treatment in the private setting are necessary to enable future large-scale public-private partnerships in oncology.